American experience. The big burn [videorecording (DVD)] - Ives, Stephen; Platt, Oliver; Egan, Timothy (PBS Distribution, 2014)
Inspired by Timothy Egan's best-selling book, The Big Burn is the dramatic story of an unimaginable wildfire that swept across the Northern Rockies in the summer of 1910. The fire devoured more than three million acres in 36 hours, confronting the fledgling U.S. Forest Service with a catastrophe that would define the agency and the nation's fire policy for the rest of the 20th century and beyond.